Pseudomonas aeruginosa bloodstream infections: risk factors and treatment outcome related to expression of the PER-1 extended-spectrum beta-lactamase - Endimiani, Andrea (BioMed Central, 2006)
BACKGROUND: Bloodstream infection (BSI) due to Pseudomonas aeruginosa (Pa) has relevant clinical impact especially in relation to drug resistance determinants. The PER-1 extended-spectrum beta-lactamase (ESBL) is a common enzyme conferring high-level resistance to anti-pseudomonal cephalosporins. Risk factors and treatment outcome of BSI episodes caused by PER-1-positive Pa (PER-1-Pa) strains were compared to those caused by ESBL-negative Pa isolates (ESBL-N-Pa). METHODS: Twenty-six BSI cases due to ceftazidime-resistant Pa strains have been investigated. MIC values of anti-pseudomonal drugs were determined by the Etest method (AB Biodisk, Solna, Sweden). The double-disk synergy test was used to detect ESBL production. PCR amplification and DNA sequencing were used to characterize ESBL types. Clinical records of BSI-patients were examined retrospectively. Demographic data, underlying diseases (McCabe-Jackson classification and Charlson weighted index), risk factors, antimicrobial therapy, and treatment outcome were evaluated in cases due to ESBL-positive and cases due to ESBL-N-Pa isolates. Unpaired Student's t-test, Mann-Whitney U-test, Fisher's exact test and the χ(2 )test were used for statistical analysis. RESULTS: Nine Pa isolates expressed the PER-1 ESBL; the remaining 17 isolates did not produce ESBLs. Severe sepsis (P = 0.03), bladder and intravascular catheters (both P = 0.01), immunosuppressive therapy (P = 0.04), and mechanical ventilation (P = 0.03) were significantly associated with BSI due to PER-1-Pa. Empirical treatment (P = 0.02) and treatment after ID/AST (P < 0.01) were rarely adequate in PER-1-Pa cases. With regard to treatment outcome, 77.8% BSI cases due to PER-1-Pa vs. 28.6% cases due to ESBL-N-Pa isolates failed to respond (P < 0.03). All cases due to PER-1-Pa that were treated with carbapenems (alone or in combination with amikacin) failed to respond. In contrast, 7/8 cases due to ESBL-N-Pa given carbapenems were responders. CONCLUSION: Therapeutic failure and increased hospital costs are associated with BSI episodes caused by PER-1-Pa strains. Thus, recognition and prompt reporting of ESBL-production appears a critical factor for the management of patients with serious P. aeruginosa infections.